Changing our behaviours as teachers in order to meet the needs of our culturally diverse students : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education (Teaching and Learning) at Massey University, New Zealand - Theobald, Christopher (Massey University, 2013)
This thesis is a qualitative, interpretative study, which examines the pedagogical processes that were involved in the implementation of the culturally relevant school programme – Ka Pai Kai – in order to derive a framework to guide teacher behaviour regarding future programme" implementation. The ‘oppressive’ dominant culture of New Zealand schools is acknowledged as a limiting factor in regard to success for those students who are from cultural minorities, especially Maori and Pasifika students. In order to combat this oppression, programmes are required to understand, be critically reflective, and act upon the needs of all students and their communities. I believe that the students in our schools in 21st Century Aotearoa deserve educational environments that are free of culturally biased oppression. The research centres around a physical activity and nutrition programme – Ka Pai Kai – that was used in one school to overtly increase both the cultural content and community participation. The experience of this programme was used as a focus for this research. Rich sources of data in the form of key informant interviews, individual and group staff interviews, and document analysis were used to provide a base of information that was worked through an interpretative analysis to identify recurring themes of culturally relevant pedagogy. During this research, respondents found it was useful to separate pedagogy into two clearly defined but related components: ‘Programme’ and ‘Implementation’. Previous evaluation confirmed that Ka Pai Kai was a positive example of a culturally relevant programme, therefore the focus of this research was on the implementation component of [critical] pedagogy. This research had six key findings: 1. When considering a pedagogical approach, teachers found it useful to distinguish between programme content and programme implementation 2. A set of elements was found that teachers believed/confirmed were required for successful implementation"of"culturally responsive programmes; 3. These elements had an ‘order’ in the sense that they did not all operate at the same level and there may have been a temporal sequence; 4. Each element can be explained in detail, yet they were not mutually exclusive; 5. In a small school, and in a pedagogical sense, the distinction between elements which relate to programme content and those that relate to implementation was blurred; and, 6. Teachers believed that these elements are probably transferable to other curriculum areas. The interpretative analysis identified four ‘First Order’ elements that powerfully impacted on the implementation of the programme in a manner that was culturally responsive to the needs of a diverse community. Seven further ‘Second Order’ elements were identified that either enhanced one or all of the first order elements, or stood alone as more minor contributors to successful implementation. The higher level analysis provided an insight into the role of pedagogy in the daily lives of teachers and I present my conclusions based around the need to bridge the gap between pedagogy and practice. One conclusion is the creation of a matrix to be used as a tool to alter teacher behaviour. The matrix can be used in planning (and evaluating the implementation phase of culturally relevant programmes. The matrix combines the First and Second Order elements to suggest transferability of success between the Ka Pai Kai programme and other school programmes that attempt to reach the same diverse audience. This thesis serves as a springboard to focus on ways to bring about the change in teacher behaviour that is required for all students to achieve equitable outcomes. A lingering concern is the gap between knowledge/attitudes that teachers showed and their behaviour/practice. The framework identified is one means of bringing about this change in practice; the shift needs to turn to ensuring that the focus of all schools is soundly placed on addressing the needs of all students they serve.
Keywords: Pacific Islanders; Pasifika; Education (Primary); Minorities; Teacher effectiveness; New Zealand